VALUE ADDING OF BUFFALO MEAT IMPORTED FROM INDIA IN PROCESSED MEAT PRODUCTS - Babji, Abdul Salam; Ramaya, Komate (Proceeding Buffalo International Conference, 2013)
Malaysia imported more than 70% of its red meat from India in the form of frozen bone less buffalo meat. Ironically importers and consumers called this imported buffalo meat as